C-H bond activation and C-N coupling reactions of methylacetylenes and allenes with an imidotitanium complex - Bashall, A; Collier, P; Gade, L; McPartlin, M; Mountford, P; Trosch, D (1998)
Reaction of an imidotitanium complex, stabilized by a tridentate diamidopyridine ligand, with the methyl acetylenes MeC2Me and MeC2Ph led to C-H-activation of the substrate and subsequent C-N coupling to give azatitanatetracycles which may be viewed as dimetallated enamines; the same compounds were obtained in reactions with the allenes Me(H)C=C=CH2 and Ph(H)C=C=CH2.